Concomitant endoscopic biliary, duodenal and colonic stent placement for advanced carcinoma of gall bladder - Sridhar Sundaram; Sidharth Harindranath; Praveen Kumar Rao; Nitin Ramani; Aditya Kale; Shraddha Patkar (Society of Gastrointestinal Intervention, 2021)
Combined biliary and duodenal stent placement has been reported previously in multiple series. Rarely, colonic obstruction may present simultaneously with duodenal and biliary obstruction in advanced pancreaticobiliary cancers. Biliary, duodenal and colonic obstruction managed simultaneously using endoscopic modalities have been reported in only one case report previously. Here we report outcomes of a case of carcinoma of the gall bladder with biliary, gastric outlet and colonic obstruction managed by endoscopic placement of biliary, gastroduodenal and colonic self-expanding metal stents.